MEMANFAATKAN SOCIAL MEDIA MARKETING PADA IBU PERSIT KARTIKA CHANDRA KIRANA RANTING 05-MASBAGIK GUNA MENAMBAH PENDAPATAN KELUARGA - Asri Oktiani; Suharti Suharti; Sri Maryanti (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The purpose of this community service activity is to analyze and evaluate the use of social media in product promotion amid the continuously evolving digitalization era. The partner in this project is the women's organization Persit Kartika Chandra Kirana, Ranting 05 Masbagik. Based on initial observations, several problems were identified, including: a lack of understanding regarding the use of social media as a marketing tool, limited technical skills in creating engaging promotional content, and the suboptimal use of social media in increasing household income. The community service activities were carried out in the form of outreach and training sessions on using social media as a promotional tool. The program showed a significant improvement in the participants’ knowledge about how to utilize social media to initiate and optimize product promotion, ultimately achieving the goal of increasing family income.